Optimalisasi Perancangan Desain Arsitektur Yayasan untuk Menghasilkan Bangunan yang Nyaman dan Hemat Energi - Rizki Hambali; Erza Rahma Hajaty; Risky Handayani; Azka Pintra (Forum Kerjasama Pendidikan Tinggi, 2026)
Yayasan Dharma Bangsa Mandiri is a social organization actively playing a role in developing community potential through various programs in education, economics, social-cultural affairs, religion, and health. All operational activities and community services are currently conducted at the foundation's office, which faces limitations in physical space and user comfort. The inadequate existing building conditions lead to suboptimal support for activities carried out by staff and the community. This problem serves as the basis for the Community Service Team from the Architecture Study Program of Universitas Indraprasta PGRI to conduct collaboration, mentoring, and redesigning of the YDBM office. The main objective of this community service activity is to provide architectural design solutions that can optimize spatial functions while increasing thermal and visual comfort for all users. The method employed is a sustainable architecture approach, emphasizing the optimization of natural ventilation and natural lighting, along with flexible, functional, and humanistic spatial arrangements. The results of this activity consist of a design concept highly responsive to the partner's specific needs, capable of integrating energy efficiency principles with dynamic social activity requirements. Through this new design, the foundation's office is expected not only to provide physical comfort but also to become a robust supporting facility for the sustainability of long-term community empowerment programs. The integration of adaptive and inclusive design elements allows each spatial zone to be used effectively for various activities, thereby increasing the foundation's operational effectiveness independently. Preliminary results indicate that this design has successfully formulated a more organized and efficient spatial layout for users. The concrete contribution of this activity is the realization of an office environment capable of supporting productivity and providing a significant positive impact on improving the quality of life for the community served by the Yayasan Dharma Bangsa Mandiri.